Pengaruh Pemberian Pupuk Organik Cair Terhadap Pertumbuhan Dan Hasil Tanaman Pakcoy - Serlin Jessica Mendrofa; Natalia Kristiani Lase (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of liquid organic fertilizer on the growth and yield of pakcoy (Brassica rapa L.) plants. The research method used was descriptive qualitative with a direct observational approach, interviews with farmers and agricultural extension workers, and visual documentation of plant growth over four weeks. The results showed that pakcoy plants treated with liquid organic fertilizer experienced better vegetative growth, including increased plant height, more leaves, darker green leaf color, and higher yield compared to untreated plants. The fertilizer used contains essential macro and micronutrients and phytohormones that accelerate plant growth. Moreover, the use of this fertilizer improves soil conditions and supports sustainable agricultural practices. The study concludes that liquid organic fertilizer significantly contributes to increasing the productivity of pakcoy plants both ecologically and economically.